2012
DOI: 10.1002/jbmr.1613
|View full text |Cite
|
Sign up to set email alerts
|

A single-dose study of denosumab in patients with various degrees of renal impairment

Abstract: This 16-week study evaluated pharmacokinetics and pharmacodynamics of denosumab in 55 subjects with renal function ranging from normal to dialysis-dependent kidney failure. Participants received a single 60-mg subcutaneous dose of denosumab. Kidney function groups were based on calculations using the Cockcroft-Gault equation and U.S. Food and Drug Administration (FDA) guidance in place when the study was designed. Renal function did not have a significant effect on denosumab pharmacokinetics or pharmacodynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
240
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 291 publications
(253 citation statements)
references
References 27 publications
5
240
1
7
Order By: Relevance
“…In addition, recent studies showed that treatment with DMAb induced severe hypocalcemia in CKD patients (particularly, CKD stage 4-5D patients complicated with SHPT) compared to the general population (Jamal et al 2010;Dave et al 2015). Furthermore, DMAb-induced hypocalcemia was demonstrated to develop during the first two weeks of DMAb administration in CKD patients (Block et al 2012). Our patient showed hypocalcemia in the 8 days following DMAb administration.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…In addition, recent studies showed that treatment with DMAb induced severe hypocalcemia in CKD patients (particularly, CKD stage 4-5D patients complicated with SHPT) compared to the general population (Jamal et al 2010;Dave et al 2015). Furthermore, DMAb-induced hypocalcemia was demonstrated to develop during the first two weeks of DMAb administration in CKD patients (Block et al 2012). Our patient showed hypocalcemia in the 8 days following DMAb administration.…”
Section: Discussionsupporting
confidence: 49%
“…Moreover, there is no strong evidence to support its efficacy. However, a clinical study by Block et al (2012) indicated that treatment with DMAb resulted in rapid reduction of bone turnover markers in patients with CKD, which was sustained from the first observation at day 2 to the end of the study at day 113. In addition, Jamal et al (2011) showed that DMAb is effective in improving the BMD of patients with CKD in a short period of time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the effect of denosumab lasts several months which benefits patients by eliminating the need for frequent clinic visits. Hypocalcemia is the most concerning adverse effect of denosumab, especially in chronic kidney disease patients [11]. The possible mechanisms include: active vitamin D deficiency, hungry bone syndrome with hyperdynamic bone disease, concomitant use of cinacalcet, increased osteoprotegerin activity, and RANKL removal in HD patients [12].…”
Section: Discussionmentioning
confidence: 99%